Pengaruh Pendidikan dan Pendapatan Orang Tua Terhadap Tingkat Pendidikan Anak Keluarga Nelayan Tradisional Kecamatan Seruyan Hilir Kabupaten Seruyan - Widy Astuti; Holten Sion; Dehen Erang (FKIP, Universitas Palangka Raya, 2021)
This study was done at Seruyan Hilirsubdistrict of Seruyan regency to know whether there was an effect of parents ’education toward the level of children education in traditional fishermen family. Whether the parents’ income had an effect toward the level of the traditional fishermen’ children education and it was also to know the effect of parents’ education and parents’ income toward the level of children education in traditional fishermen of SeruyanHilirsubdistrict of Seruyan regency. The aim of this study was to know the effect of parents’ education and parents’ income toward the level of children education in traditional fishermen. The differences in the high level of education and the amount of parents’ income whether had an effect on their children’s education level. The study was one of a quantitative research method. The instrument of data collection on this study used questionnaires. The data analysis applied descriptive presentation and regression multiple. The technique of sample collection used Proportionate Stratified Random Sampling technique because the stratified population. The amount of sample was determined by using Isaac and Michael tables. The result of analysis showed that the significance value on the result of SPSS 16.0, the effect of parents’ income toward the level of the traditional fishermen’ children education was 0.00 < 0.05, which was obviously variable X1 and X2 influenced the variable Y. The effect of parents’ income toward the children education got P value < 0.05 (0.00 < 0.05), the H0 rejected and H1accepted, it meant that there was a significant effect of fishermen income toward the level of the traditional fishermen’ children education. According to the result of computation apparently show that X1 and X2 had an effect toward Y. Based on the table R2 value (R square) was 0.676 or (67.6%). It showed that the contributory percentage of the independent variable effect (Fishermen’ education and income) toward dependent variable (the education of fishermen children) were 67.6%.